Physico-Functional and Nutritional Properties of Pigmented and Non-pigmented Maize Available In Bangladesh (Bangladesh Journal of Botany, 2022)
Consumption of diversified pigmented whole grain maize is encouraged to combat hidden hunger. The present research was conducted to evaluate physico-functional and nutritional properties of pigmented and non-pigmented maize in Bangladesh. Results revealed that white maize had the highest brightness value while purple, and deep red maize showed the lowest brightness value. The lowest bulk density (0.565 ± 0.005 g/ml) and percentage change (15.05 ± 0.31%) in sedimentation was in purple maize flour. White maize flour showed the highest change (35.43 ± 0.59%) in sedimentation value. Red and purple maize contained the highest amount of ash (2.27 ± 0.059 and 2.27 ± 0.05%, respectively) and mixed maize contained the highest crude fibre (4.17 ± 0.049%). Purple, deep red, and mixed colored maize had the highest (72 to 73%) carbohydrate whereas indigenous deep red and mixed colored maize had the lowest (6%) protein content. All most all samples had similar Mg and S content. Purple, deep red and mixed maize were found to be promising for Ca. White maize had the highest amount (19.79 ± 0.1 mg/100 g) of Zn. Yellow maize showed to contain the highest amount (4.99 ± 0.37 mg/100 g) of Fe. Overall, whole grain pigmented and nonpigmented hybrid and indigenous maize were comparable for physico-functional and nutritional properties.Bangladesh J. Bot. 51(3): 589-596, 2022 (September)